Quality of Life and Treatment Outcome of Psychiatric Morbidities in Cancer Patients - Thapa, Prashwas; Rawal, Namrata; Bista, Yadav (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Cancer is associated with signiÞ cant psychosocial morbidity and has impact on quality of life.An appropriate psychiatric management of cancer patient may improve the ultimate quality of living. Methods: The objective of this study was to see the outcome of treatment of depression and anxiety and itseffect in quality of life in cancer patients. A cross sectional study was used. A total of eighteen (18) cancerpatients with depression, anxiety; and both depression and anxiety were assessed for quality of life and providedtreatment. The tools used were General Health Questionnaire (GHQ), Hospital Anxiety and Depression Scale(HADS) and World Health Organization Quality of Life (WHOQOL) scale. Results: The study concluded that 43.75% of depressed and 41.66% of anxiety cancer patients improved ontreatment and there also was a signiÞ cant improvement in quality of life, specially in psychological and physicaldomain. Conclusions: Oncology centres should work in close liaison with psychiatrists which can improve the qualityof life of cancer patients. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12918